PARAMETRICAL DIAGNOSIS BASED ON SYNCHRONIC AND ASYNCHRONIC OF GAS TURBINE ENGINES OF ONE AIRCRAFT - B. K. Njenge (Научный вестник МГТУ ГА)
The article deals with identification and shows examples on parametrical diagnosing of GTE on the same aircraft using synchrony and asynchrony of time series.